Children's Health Opportunities and Project Evaluation : Mexico's Oportunidades Program - Van de gaer, Dirk; Vandenbossche, Joost; Figueroa, José Luis (Oxford University Press on behalf of the World Bank, 2015)
We propose a methodology to evaluate social projects from the perspective of children's opportunities on the basis of the effects of these projects on the distribution of outcomes. We condition our evaluation on characteristics for which individuals are not responsible; in this case, we use parental education level and indigenous background. The methodology is applied to evaluate the effects on children's health opportunities of Mexico's Oportunidades program, one of the largest conditional cash transfer programs for poor households in the world. The evidence from this program shows that gains in health opportunities for children from indigenous backgrounds are substantial and are situated in crucial parts of the distribution, whereas gains for children from nonindigenous backgrounds are more limited.